1993
DOI: 10.1541/ieejpes1990.113.4_313
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown Characteristics under Metallic Particle Contaminated Conditions in Vacuum Gap

Abstract: An experimentwas carried out to investigate the influence of metallic particles on vacuum breakdown characteristics. By laser scattering method, the movement of particles, the lifting voltage of particles and the velocity of impact to the opposite electrode were measured. The particles were made of pure copper, and the particle diameter was 0.1 to 300 µm. The electrodes were parallel plane, 40 mm diameter, and two sets of electrodes (pure copper and stainless steel)were examined.Experimental results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Finally, in each of the three cases, the degree of freedom adjusted determination coefficient (Adj. R ) was 0.93 or greater. Therefore, we can say that the regression curves satisfactorily explain the influence of each of the parameters.…”
Section: Simulation Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Finally, in each of the three cases, the degree of freedom adjusted determination coefficient (Adj. R ) was 0.93 or greater. Therefore, we can say that the regression curves satisfactorily explain the influence of each of the parameters.…”
Section: Simulation Resultsmentioning
confidence: 92%
“…For example, Kamikawaji et al . and Shioiri et al . demonstrated that the breakdown voltage in a gap may decline 30% or less due to the presence of electrically conductive microparticles.…”
Section: Introductionmentioning
confidence: 99%
“…① Growth of protrusion on the contact surface by applying voltage ② Melting of protrusion by emission current and emission of vapor and gas ③ Movement of particle between contact ( [6] suggests that dielectric breakdown occurs late after current interruption when metallic particles are poured onto the electrode surface.) Therefore we decided to examine the contact surface after current interruption to clarify these points [3,4].…”
Section: Non-sustained Disruptive Dischargementioning
confidence: 99%
“…Insulation breakdown occurs late as shown in Figure 22 when the collision energy of metallic particles is large because the metallic particles repeatedly collide on the electrode surface. In addition, the condition of electrode surface influences on dielectric breakdown [6]. The main reason for the later occurrence of NSDD after current interruption may be due to the above mentioned phenomenon.…”
Section: Occurrence Time Of Non-sustained Disruptive Dischargementioning
confidence: 99%
“…Therefore, the relation between breakdown and the prebreakdown current for an unconditioned electrode surface at currents of less than 10 6 A is not clear. Papers on the relation between electrode conditioning and the prebreakdown current [10,11] note that breakdown occurred suddenly on unconditioned electrodes despite the fact that no prebreakdown current was detectable by a pico-ammeter, suggesting that the sudden breakdown was related to lower current levels.…”
Section: Introductionmentioning
confidence: 99%